2022
DOI: 10.1111/1440-1681.13642
|View full text |Cite
|
Sign up to set email alerts
|

Citri Reticulatae Pericarpium alleviates postmyocardial infarction heart failure by upregulating PPARγ expression

Abstract: Heart failure after myocardial infarction (MI) is the leading cause of death worldwide. Citri Reticulatae Pericarpium (CRP) is a traditional Chinese herbal medicine that has been used in the clinic for centuries.In this study, we aimed to investigate the roles of CRP in cardiac remodeling and heart failure after MI, as well as the molecular mechanisms involved. MethodsMale C57BL/6 mice aged 8 weeks were subjected to coronary artery ligation to mimic the clinical situation in vivo. Echocardiography was used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Moreover, zerumbone, ganxin V, nutmeg-5, ginsenoside Rg2, jatrorrhizine, cardiotonic pill, and huoxin pill all regulate the TGF-β1/smad pathway to attenuate fibrosis ( Li et al, 2020d ; Wang et al, 2021b ; Yan et al, 2022a ; Yan et al, 2022b ; Li et al, 2022c ; Hao and Jiao, 2022 ; Liang et al, 2022 ). Moreover, citri reticulatae pericarpium also reduces CMs apoptosis, CFs proliferation, and CF-to-MF transformation by upregulating PPAR-γ expression ( Chen et al, 2022c ), while auraptene improves cardiac hypertrophy and dysfunction via activating PPARα ( Sunagawa et al, 2022b ). Tanshinone IIA suppresses inflammation and fibrosis via the regulation of NADPH oxidase 4 ( Chen et al, 2021b ).…”
Section: Interventions For Cardiac Fibrosismentioning
confidence: 99%
“…Moreover, zerumbone, ganxin V, nutmeg-5, ginsenoside Rg2, jatrorrhizine, cardiotonic pill, and huoxin pill all regulate the TGF-β1/smad pathway to attenuate fibrosis ( Li et al, 2020d ; Wang et al, 2021b ; Yan et al, 2022a ; Yan et al, 2022b ; Li et al, 2022c ; Hao and Jiao, 2022 ; Liang et al, 2022 ). Moreover, citri reticulatae pericarpium also reduces CMs apoptosis, CFs proliferation, and CF-to-MF transformation by upregulating PPAR-γ expression ( Chen et al, 2022c ), while auraptene improves cardiac hypertrophy and dysfunction via activating PPARα ( Sunagawa et al, 2022b ). Tanshinone IIA suppresses inflammation and fibrosis via the regulation of NADPH oxidase 4 ( Chen et al, 2021b ).…”
Section: Interventions For Cardiac Fibrosismentioning
confidence: 99%
“…To date, CRP has proven effects in the respiratory system, including but not limited to inhibiting airway inflammation, fighting acute lung injury and pulmonary fibrosis [ 8 , 9 , 10 , 11 , 12 , 13 ]. In terms of the cardiovascular system, CRP can improve cardiac insufficiency, alleviate cardiac hypertrophy and myocardial fibrosis, prevent hyperlipidemia and keep cardiomyocytes away from the damage of hypercholesterolemia [ 14 , 15 , 16 , 17 , 18 ]. Experiments have found that CRP’s neuroprotective properties confer the ability to prevent neurodegeneration caused by Parkinson’s, Alzheimer’s, Huntington’s disease and multiple sclerosis [ 19 , 20 , 21 , 22 ].…”
Section: Pharmacological Effects and Chemical Composition Of Crpmentioning
confidence: 99%